STUDENT CENTERED LEARNING: AN APPROACH TO DEVELOP SPEAKING SKILL IN EFL CLASSROOM - Larasati, Finza (English Community Journal, 2018)
This paper brings to light, the importance of an approach in learning speaking; a student centered learning approach. The researcher pays so much attention on this approach caused the necessity of students in globalization era that required them to master the English especially in terms of communication. A key issue here is whether what happens in a speaking classroom is concerned with “teaching speaking”. Student-centered learning is focused on the student’s needs, abilities, interests, and learning styles with the teacher as a facilitator of learning. This classroom teaching method acknowledges student voice as central to the learning experience for every learner. The relationship between student-centered approach and the speaking skill is relevant. This approach creates learning by doing situation. The students can develop their speaking skill through the realization of tasks, which are devised along with the students and taking into consideration their needs and characteristics.